Migration of maximum scour location around wide setback bridge abutments in floodplains - Ahmed Abouelfetouh Abdelaziz (2022)
Location of maximum scour depth is a key feature for the accurate design of scour countermeasures. Experimental results show that the maximum scour depth around wide setback abutments migrates to a location further downstream than that observed conventionally at the tip for narrower abutment. The wide abutment caused two scour holes to form, with a larger primary scour hole and a smaller secondary scour hole downstream from the first, and this has important implications for scour protection at the structure's foundation. For this study, 55 experiments were conducted with seven abutment aspect ratios and the migration of the maximum scour locations were measured. The results reveal that Rx (the normal distance from abutment face to the location of maximum scour depth) is affected by the flow intensity, flow depth, and abutment aspect ratio. The value of Rx is larger as flow intensity decreases for the same abutment aspect ratio. However, Ry (the distance from the centerline of abutment face to the location of maximum scour depth parallel to flow direction) is only affected by flow depth and abutment aspect ratio. Empirical equations are proposed to predict the locations of the maximum scour depth for wide abutments in compound channels.